Kontribusi Dosen Hukum PTKIN Dalam Penyelesaian Sengketa Adat di Aceh - Fakhrurrazi, Fakhrurrazi; Rasyidin, Rasyidin; Haikal Ananda, Muhammad (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
The existence of Adat in Aceh is getting stronger after the MoU between the Indonesian government and the Free Aceh Movement. However, it cannot be denied that customary disputes continue to occur. Lecturers as academics are required to be involved in the customary settlement process because this is a form of lecturer service to the community. This paper aims to look further at the involvement of PTKIN lecturers in Aceh in the customary dispute resolution process. This research resulted from an empirical study using a sociological approach. The sociological approach looks at how the activities of the Acehnese indigenous people contribute to resolving customer disputes. This study focuses on two PTKIN consisting of lecturers at UIN Ar-Raniry and IAIN Lhokseumawe. Data sources were obtained from interviews and observations; data analysis was carried out by means of data reduction obtained from the interviewer, and then analysis was carried out. The results of this study indicate that practically, law lecturers, with their scientific discipline, have contributed to the resolution of customary disputes. The law lecturer at PTKIN has carried out several stages of customary dispute resolution, starting from examining the problem, carrying out mediation, and reviewing legal norms that are used as a reference in dispute resolution. The strategy for resolving disputes is carried out by classifying the problem and bringing it closer to the legal aspect so as to produce a balanced solution both in terms of aspects of religious law and state law. Obstacles and problems that occur are related to the lack of agreement between the parties regarding customary decisions, so the parties choose the path of litigation (court). The litigation route is the last alternative when an agreement cannot be reached through a customary decision.